Design and development of chassis for formula student vehicle - Dabhade, Ameya; Pathan, Khizar Ahmed; Khan, Sher Afghan; Jadhav, Akash (IAEME Publication, 2020)
A chassis design involves selecting optimum measures of parts and iterating it to achieve the objectives assumed. Every part of the chassis is related to each other; it is necessary to study effects to get an optimum design. This research paper aims at the design, analysis, and manufacturing of a chassis. This paper also covers the pre-designing phase of constructing a human ergonomics for a driver, drafting a chassis to accommodate 95th percentile men and 5th percentile female, and thoroughly analyzing the model to check for safety. This paper also introduces the way to make fixtures for effective and efficient manufacturing.